Sanctus et sanctitas dans les Bibles latines - Marie Rébeillé-Borgella (Conserveries Mémorielles)
Sancio, sanctus and sanctitas are used in the Vulgate as translations of Hebrew and Greek lexemes that belong to religious vocabulary. What notions and actions do these terms exactly translate ? What new meanings do they carry ? How do the lexemes evolve semantically ?